Skvamózní intraepitelová léze u mladých zen, studujících vysokých skol - Kulhánková, J; Rob, L; Beranová, V; Braunová, S; Güttner, V; Jedlicková, J; Pelák, Z; Slavíková, P; Sikýr, M; Vítková, I (Ceska gynekologie, 1997)
The authors investigated the frequency of squamous intraepithelial lesions (SIL) in young women, in particular university students with special attention to morphological signs of the presence of human papilloma virus (HPV) in SIL low grade-SIL, LG-HPV. As compared with data in the world literature, they revealed a significantly lower rate of SIL LG, HPV-2.81% as compared with 5.5% reported in WHO studies of young women. The authors analyzed the biological behaviour of SIL, LG-HPV. As compared with data in the literature on known values of spontaneous regression which are 50-62% in the course of three years, they demonstrated during a time interval from 3 months to 2 years spontaneous regression in 39.1%. Further possibilities of regression in a longer time interval are expected in the group of clinically latent cytologically persistent LG lesions (18.1%) and in the group of patients which after termination of their studies were lost from the records (24.3%). During the investigated time interval no case of progression to a higher grade lesion was recorded. The authors reflect on diagnostic and therapeutic procedures with regard to the application of results of HPV typing.
Keywords: Humans; Tumor Virus Infections; studenti; Female; dospělí; nádory děložního čípku; lidé; Papillomaviridae; Adult; Papillomavirus Infections; ženské pohlaví; dysplazie děložního hrdla; Adolescent; Czech Republic; infekce papilomavirem; Uterine Cervical Neoplasms; Uterine Cervical Dysplasia; Students; Česká republika; mladiství; infekce onkogenními viry